Beitrag zur Lachnidenfauna Mitteleuropas (Homoptera: Aphididae). - Kloft, Werner; Kunkel, H.; Ehrhardt, P. (Contributions to Entomology = Beiträge zur Entomologie, 1960)
The authors report on two rare Aphid species : Cinara kochiana (Börn.), and C. escherichi Börn. Furthermore they give details on the more widely distributed species C. pectinatae (Nördl.), C. pilicornis (Htg.), and Lachniella costata (Zett.), their distribution, food plants, trophobiosis, and apicultural importance.